Relation between stent thrombosis and calcium channel blocker after drug-eluting stent implantation. Issue 4 (October 2015) - Nagano, Masahide; Hokimoto, Seiji; Nakao, Koichi; Kaikita, Koichi; Akasaka, Tomonori; Ogawa, Hisao; on behalf of Kumamoto Intervention Conference Study (KICS) Investigators, 1
Abstract Background Stent thrombosis (ST) has emerged as a severe complication of percutaneous coronary intervention (PCI). Since the occurrence of ST is lower in Japan than Western countries, there are few data to predict ST after drug-eluting stent (DES) implantation in Japan. We examined the independent predictors of ST incidence after DES implantation in Japanese patients, including the use of calcium channel blockers (CCBs). Methods and results We used data from the Kumamoto Intervention Conference Study registry. There were 6286 consecutive patients enrolled from June 2008 to March 2011. Among them, we analyzed 3493 patients who underwent DES implantation. The incidence of definite/probable ST throughout a median follow-up period of 364 days was 0.57% (20 patients). There were 8 patients with early ST (within 30 days), 8 patients with late ST (between 31 and 365 days), and 4 patients with very late ST (after 1 year). The frequency of CCB use was significantly lower in ST than non-ST patients (25.0% versus 51.4%, respectively, p = 0.016). Multiple regression analysis showed that longer stent length (p = 0.034), acute coronary syndrome (p = 0.039), and the absence of CCB use (p = 0.046) were significant and independent predictors of ST within 1 year. Conclusions These results suggest that CCB use may be associated with a decreased risk of ST after DES implantation within 1 year in Japanese patients.